2015
DOI: 10.1016/j.ecoenv.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concentrations of benz[a]anthracene induce developmental defects and DNA damage and impair photomotor response in Japanese medaka larvae

Abstract: Benz[a]anthracene (BaA) is a ubiquitous polycyclic aromatic hydrocarbon found in numerous aquatic ecosystems. However, ecotoxicological data in aquatic organisms are scarce. To remedy this lack of data, Japanese medaka (Oryzias latipes) embryos were exposed to BaA and toxic effects were investigated at multiple toxicological endpoints. Japanese medaka embryos were incubated onto BaA-spiked artificial sediment for 9 days at low or moderate environmental concentrations ranging from 0.9 to 12 µgg(-1) dw. BaA-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
3
10
1
Order By: Relevance
“…In their studies, adult zebrafish which were developmentally exposed to individual PAHs or PAH mixtures, exhibited impaired locomotor activity, and increased anxiety compared to non-exposed fish. Additionally, similar results were reported using Japanese medaka embryos exposed to BAA (Le Bihanic et al, 2015), suggesting that PAHs are developmental neurotoxicants. The probability that some oxy-PAHs are also developmental neurotoxicants is high, however, a more comprehensive analysis is still needed.…”
Section: Resultssupporting
confidence: 84%
“…In their studies, adult zebrafish which were developmentally exposed to individual PAHs or PAH mixtures, exhibited impaired locomotor activity, and increased anxiety compared to non-exposed fish. Additionally, similar results were reported using Japanese medaka embryos exposed to BAA (Le Bihanic et al, 2015), suggesting that PAHs are developmental neurotoxicants. The probability that some oxy-PAHs are also developmental neurotoxicants is high, however, a more comprehensive analysis is still needed.…”
Section: Resultssupporting
confidence: 84%
“…2C) . A reduction in the swimming activity behavioral pattern was also recorded in Japanese medaka after exposure to benzo[a]anthracene (4-benzenic rings) (Bihanic et al 2015). The present study demonstrated a parental influence in the neurotoxic behavior of their offspring.…”
Section: Behavioral Disruptions In Offspring Larvae (F 1 Generation)supporting
confidence: 71%
“…In aquatic organisms, exposure to PAHs can thus lead to detrimental defects from a developmental, physiological and behavioral point of view (Bihanic et al 2015;Incardona et al 2011;Perrichon et al 2014). PAHs' impact on reproductive success is particularly studied due to its consequence on population recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the embryotoxic and teratogenic effects observed in medaka embryos and larvae are highly correlated to organic pollutants and TOC content in sediments of the Bizerte lagoon (Table ). This result is in accordance with numerous studies reporting developmental and genotoxic effects of low or moderate concentrations of PAHs in Japanese medaka early life stages . In addition, among the low–molecular weight PAHs detected in the present study, the concentrations of fluorene and acenaphthene in the sediment exceeded the effects range low level .…”
Section: Discussionsupporting
confidence: 93%